(3TQM GdEYQGH Yf bhGYO GdEYQGHs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s; (3CHh eMeO LeGd GdOjf YHO Gddg Hf jhSa GHf gTGe GdfMhj,J (B762 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdQGaY dbhGYO GdOjf hGdESdGe , GdfGUH GdQGjGJ GdgOi CeG HYO aEf GdYHO GdeSJeO ef ajV aVd GdYRjR GdhgGH eMeO Hf SdjeGf GdeTghQ HcCajLi Hjf GdCUMGH jbhd deG QCjJ GdcJGH GdeSei HGdEYQGH s
(3BNQgG (B:s
(3aEf GdJCed CUd ai OQc GdCehQ cdgG adgPG bGd ai Chd GdcJGH jbJai eJCedgG LGOI GdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B124s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs